African‐centered coping, resilience, and psychological distress in Black prostate cancer patients. Issue 4 (9th November 2021) - Martin, Chloé M.; Schofield, Elizabeth; Napolitano, Stephanie; Avildsen, Isabelle K.; Emanu, Jessica C.; Tutino, Rebecca; Roth, Andrew J.; Nelson, Christian J.
Abstract: Objective: Blacks have the highest incidence and mortality rates for prostate cancer (PCa) in the U.S. Black PCa patients (PCaP) also report high psychological distress. Identifying culturally specific coping strategies that lower distress among Black PCaP could help improve psychological interventions for this group. African‐centered coping (strategies unique to the structure of Black personality and the African‐centered worldview) have been identified. We hypothesized that these coping strategies and resilience would be associated with lower psychological distress (anxiety and depression) in Black PCaP. Methods: Black PCaP ( N  = 95) completed a survey assessing African‐centered coping strategies, resilience, anxiety, and depression. Multiple regression was employed to examine African‐centered coping strategies and resilience as predictors of psychological distress. Results: Participants were aged M  = 67 ± 9 years and 52% had late‐stage PCa. Twenty percent met criteria for clinically significant anxiety, and 17% for depression. African‐centered coping strategies were not associated with lower anxiety or depression, while resilience was associated with decreased anxiety ( r  = −0.45, p  < 0.001) and depression ( r  = −0.54, p  < 0.001). Mediation analyses did not support an indirect association among African‐centered coping strategies, resilience, and anxiety and depression. Conclusions: Contrary to hypotheses, African‐centered coping strategies were not associated with psychological distress. However, as predicted, greater resilience was associated with lower anxiety and depression. These findings support the relevancy of resilience in Blacks' psychological adjustment to PCa. It might be worthwhile to explore African‐centered coping strategies that help Black PCaP cope with distress.